Gender and authoritarian populism: empowerment, protection, and the politics of resentful aspiration in India. Issue 2 (2nd April 2020) - Chacko, Priya
ABSTRACT: The promotion of conservative gender values has been a feature of the rise of authoritarian populism globally. This paper argues that India's ruling Bharatiya Janata Party (BJP) uses populist strategies to promote a political project of marketized Hindutva, which melds neoliberalism and Hindu nationalism and appeals to men and women in distinctive ways. This reflects the gendered nature of neoliberalism, electoral imperatives and the patriarchal gender values of Hindu nationalism. Using populist discursive and mobilizational strategies, the BJP aims to suture together a broad social base, represented as "the people, " through the creation of an aspirational identity. Concurrently, it stokes resentment against establishment elites and religious minorities for holding back the people's aspirations. This politics of resentful aspiration underpins an empowerment agenda of marketized social policies targeted at turning poor and lower-middle class women into virtuous market citizens who embody neoliberal rationalities and Hindu nationalist social values. It also drives a protection agenda mobilizing young, lower-middle class men and the strong arm of the state to protect women's capacity to become virtuous market citizens. These agendas claim to empower and protect women but are deeply disempowering for the women and men they target and contain inherent contradictions.